IMPLEMENTASI PENYELESAIAN PELANGGARAN HAM BERAT DI INDONESIA - Poltak Siringoringo (to-ra, 2016)
Under the provisions of Article 4 of law no.26 of 2000 on Human Rights Court and the duty to investigate and resolve cases of serious Human Rights Violations. Of the provisions of this article means that not all Human Rights violations be tried by a court of Human Rights but is limited to â€œSerious Human Rights Violationsâ€. Is a grass Human Rights Violations under the provisions of law No. 26 of 2000 is described in chapter 7, which reads as follows: â€œSerious Human Rights Violations Include: (1) The crime of genocide and (2) Crimes against Human. In addition to the Human Rights Court to investigate and resolve cases of Serious Human Rights Violations that occurred in the Territorial unitary state of Indonesia (Principle Territorialitet). Also to investigate and resolve cases of grass Human Rights Violations commited by Indonesia citizen outside the unitary Republic of Indonesia (Principle Nasinalitet). Besides mechanisms and inter rasional, other mechanism that a new mechanism for justice in cases of human evil is a mixture courts or better known as hybrid tribunal. Model of this trial appeared to be criticism of the weakness of national courts and international courts, as shown in the international criminal tribunal for the farmer Yugoslavia and the International criminal court for Rwanda.Kata Kunci: Implementasi Peyelesaian Pelanggarah HAM Berat